Elaboración de una cerveza orgánica a partir de la quinoa (chenopodium quinoa). - Márquez Farías, Alex Jesús (2015)
The main target of this research was to make artisanal beer from Quinoa as a main material. We could get the details of the process. On the other hand the physical-chemical factors are described to obtain an expected product with all requeriments fulfilled. The main material was washed, then malted and germinated. The chemical and microbiologic analyses were done in the laboratories of Protal-Espol and Central University in Quito. The results show that all treatments get beers which comply with the Ecuadorian regulations, and don´t show significant differences between them.